Efficacy and safety evaluation of neoadjuvant immunotherapy plus chemotherapy for resectable non–small cell lung cancer in real world - Fang, Min; Hang, Qingqing; Jiang, Haitao; Cai, Lei; Hu, Jinlin; Ying, Hangjie; Gu, Qing; Yu, Xiaofu; Liu, Jinshi; Lai, Xiaojing (Frontiers in Oncology, 2023)
OBJECTIVES: The combination of immunotherapy and chemotherapy have shown great efficacy in stage IV non-small cell lung cancer (NSCLC), and now is widely used in clinical treatment strategy. This study retrospectively analyzed the efficacy and safety of neoadjuvant immunotherapy plus chemotherapy for resectable NSCLC in real world. METHODS: We retrospectively analyzed NSCLC patients who received neoadjuvant immunotherapy plus chemotherapy and underwent complete tumor resection in Zhejiang Cancer Hospital between January 2019 and January 2021. The safety and toxicity including operative and postoperative complications, the efficacy including objective response rate (ORR), disease control rate (DCR), tumor major pathological remission (MPR) and pathological complete response (pCR) were evaluated. RESULTS: Totally, 368 NSCLC pateints were administered neoadjuvant immunotherapy. Of them, 211 patients were included in this retrospective study. Most patients had stage II-III disease, with 75 (35.5%) and 88 (41.7%) patients diagnosed clinical stage IIB and IIIA, respectively. 206 patients (97.6%) received at least 2 doses of neoadjuvant immunotherapy plus chemotherapy. 121 patients (57.3%) have achieved MPR and 80 patients (37.9%) have achieved pCR, with ORR at 69.2% and DCR at 97.7%. Treatment-related adverse events occurred in 46.4% of patients, and the incidence of grade 3 or 4 treatment-related adverse events was 13.3% (13/98). And adverse events of any grade of surgical complication occurred in 15.6% of patients. One-year disease free survival was 80.6% (170/211). CONCLUSIONS: Neoadjuvant immunotherapy plus chemotherapy has significant efficacy with a high pCR and tolerable adverse effects for patients with resectable stage II-III NSCLC in real world.